2009
DOI: 10.1093/pcp/pcp062
|View full text |Cite
|
Sign up to set email alerts
|

KORRIGAN1 and its Aspen Homolog PttCel9A1 Decrease Cellulose Crystallinity in Arabidopsis Stems

Abstract: KORRIGAN1 (KOR1) is a membrane-bound cellulase implicated in cellulose biosynthesis. PttCel9A1 from hybrid aspen (Populus tremula L. x tremuloides Michx.) has high sequence similarity to KOR1 and we demonstrate here that it complements kor1-1 mutants, indicating that it is a KOR1 ortholog. We investigated the function of PttCel9A1/KOR1 in Arabidopsis secondary growth using transgenic lines expressing 35S::PttCel9A1 and the KOR1 mutant line irx2-2. The presence of elevated levels of PttCel9A1/KOR1 in secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(98 citation statements)
references
References 67 publications
5
91
1
1
Order By: Relevance
“…The expression profile of wild-type GUS-KOR1 largely confirmed preceding studies of KOR1-mRNA expression and overlaps with the GUS expression profile driven by the Arabidopsis KOR1 promoter (Takahashi et al, 2009) (Supplemental Figure 1B). The expression pattern of the GFP-KOR1 construct was similar to that of the GUS-KOR1 construct, indicating that GFP-tagged KOR1 also mirrors the expression profile of endogenous KOR1.…”
Section: Reporter Systems Visualize Expression and Subcellular Localisupporting
confidence: 82%
See 1 more Smart Citation
“…The expression profile of wild-type GUS-KOR1 largely confirmed preceding studies of KOR1-mRNA expression and overlaps with the GUS expression profile driven by the Arabidopsis KOR1 promoter (Takahashi et al, 2009) (Supplemental Figure 1B). The expression pattern of the GFP-KOR1 construct was similar to that of the GUS-KOR1 construct, indicating that GFP-tagged KOR1 also mirrors the expression profile of endogenous KOR1.…”
Section: Reporter Systems Visualize Expression and Subcellular Localisupporting
confidence: 82%
“…Data obtained from genetic interaction analyses suggest that complex N-glycans attached to KORRIGAN1/RADIALLY SWOLLEN2 (KOR1/RSW2) protein are important during the salt stress response Kang et al, 2008;von Schaewen et al, 2008). KOR1/RSW2 encodes a type-II transmembrane protein with endo-b1,4-glucanase activity linked to cellulose biosynthesis (Lane et al, 2001;Peng et al, 2002) and has been suggested to function in relieving tension from cellulose microfibrils (Takahashi et al, 2009). Recent studies showed that KOR1 physically interacts and colocalizes with the cellulose synthase complex in vivo (Lei et al, 2014;Vain et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Similar retardation in the CSC movement in the plasma membrane was observed in a kor1 mutant (Paredez et al, 2008). Interestingly, KOR1 also plays a role in cellulose crystallinity, presumably by increasing the amount of amorphous cellulose (Takahashi et al, 2009). Both kor1 and ctl1 show dramatically reduced cellulose synthesis activity compared with the wild type as quantified by the relative incorporation of 14 CGluc into the cellulosic fractions (Mouille et al, 2003).…”
Section: Discussionmentioning
confidence: 56%
“…The cellulose crystalline/amorphous ratio also influences in muro interaction between XGs and cellulose (Hanus and Mazeau, 2006). Only one protein has been reported to alter that ratio; KORRIGAN (KOR), a membrane-bound b-1,4-glucanase, which increases the amount of noncrystalline cellulose (Nicol et al, 1998;Takahashi et al, 2009). The kor1/lion's tail1 mutant was initially isolated in a screen for mutants with anisotropic growth defects (Nicol et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Size reduction not only increases the specific surface area of biomass but also reduces cellulose DP and Crl, but it depends on biomass compositions [140][141][142][143][144][145][146][147][148][149][150][151][152]. Liu et al [132] investigated the effect of steam explosion pretreatment on corn stalk particle size for enhancing enzyme digestibility and the result shown that the amount of secondary product was higher and sugar recovery was lower for larger biomass particle size; although, during enzymatic hydrolysis sugar conversion and yield were higher.…”
Section: Physical Pretreatmentmentioning
confidence: 99%